The labyrinth in the poetry of Iván Carvajal - Mussó, Luis Carlos (Kipus: Revista Andina de Letras y Estudios Culturales, 2019)
The poetic word of Iván Carvajal Aguirre develops, by means of a lucid text, the subject of the labyrinth. It demonstrates how the subject’s discourse is hyperconscious of the writing process. Using two symbolic figures, both animal-like, the lyrical enunciator is a cicerone that leads the reader towards the certainty that the labyrinth may be entered but not exited (there is no Ariadne’s thread). Present are the monstrous minotaur, that reigns over his labyrinth on the surface, and the mole, which does the same in his underground labyrinth, that represent the poet in his trials and propositions during the writing process.